The family book - Parr, Todd. (New York : Megan Tingley Books/Little, Brown, 2003)
Represents a variety of families, some big and some small, some with only one parent and some with two moms or dads, some quiet and some noisy, but all alike in some ways and special no matter what.
Keywords: Family -- Fiction; Individuality -- Fiction; Parents -- Fiction